Catalyst for preparing synthesis gas from lignin driven by solar energy as well as preparation method and application of catalyst
Through solar-powered lignin-made synthesis gas catalyst, the use of thermal solvent self-assembly technology of non-precious metal salts and organic ligands, the problems of high energy consumption and non-renewable resources in the existing synthesis gas preparation methods are solved, and efficient and environmentally friendly synthesis gas preparation is achieved.
Patent Information
- Application Number
- CN202411663184.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
The existing industrial synthesis gas preparation methods rely on fossil resources, resulting in high energy consumption, carbon emissions and environmental pollution, and the raw materials are not renewable.
A solar-powered lignin-made synthesis gas catalyst was developed, which induced self-assembly by thermal solvent method using non-precious metal salts and organic ligands to form a high-active and high-stability catalyst for converting lignin into synthesis gas under mild conditions.
High yield synthesis gas activity, good selectivity and catalyst reusability are achieved, energy consumption and carbon emissions are reduced, and renewable lignin resources are utilized.
Smart Images

Figure CN119500155A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and particularly relates to a solar-driven lignin-to-syngas catalyst, a preparation method and application thereof. Background Art
[0002] Synthesis gas is a mixed gas with hydrogen and carbon monoxide as the main components. It is an important chemical raw material and plays a very important role in the chemical industry. For example, synthesis gas can be used to prepare chemical products such as ammonia, urea and methanol through catalytic reaction. Synthesis gas can also be used to prepare liquid fuels such as diesel and gasoline through Fischer-Tropsch synthesis. At the same time, synthesis gas can also be used as fuel gas and is a high calorific value energy source (Catalysis today, 2000, 63 (2-4), 159-164. Catalysis today, 2002, 71 (3-4), 243-247.).
[0003] At present, industrial syngas is mainly produced by steam reforming with fossil resources as raw materials (such as coal and natural gas), which usually requires high reaction temperature (700-1000°C) and pressure (>2MPa), resulting in high energy consumption and carbon emissions. At the same time, the use of non-renewable fossil resources as raw materials also causes a series of environmental pollution and raw material supply security issues (AngewandteChemie International Edition, 2024, e202405904.). Therefore, it is very important and urgent to develop green and efficient syngas production technology using renewable resources as raw materials.
[0004] Biomass is the most abundant renewable resource on earth and has been one of the main sources of energy for mankind since the Stone Age. The Blue Book distributed by the China Industrial Development Promotion Biomass Energy Industry Branch pointed out that by 2020, the annual production of major biomass resources in my country will be about 3.494 billion tons. As the most abundant renewable organic raw material on earth, biomass has the advantages of green / low carbon / clean, and is considered to be an important development direction for the future energy and chemical industries. Lignocellulose is the most abundant form of biomass. It is estimated that the annual production of lignocellulose biomass by plant photosynthesis in the world can reach 170 billion tons (Biotechnology Advances, 2009, 27 (5): 542-550.). Lignin is an important component of lignocellulose. At present, the annual production of industrial lignin in my country is about 20 million tons. Photocatalysis uses inexhaustible sunlight as the driving energy for the reaction. It has the advantages of being green and having mild reaction conditions, which has attracted widespread attention from researchers. The preparation of syngas from photocatalytically renewable lignin is of great significance to the green and renewable preparation of syngas, and at the same time reduces the energy consumption and carbon emissions of the preparation process. Summary of the invention
[0005] The purpose of the present invention is to provide a solar-driven lignin synthesis gas catalyst, the preparation method of the catalyst is simple and the raw materials are cheap and easily available. The prepared catalyst exhibits high synthesis gas production activity under a simulated sunlight irradiation reaction.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] A solar-driven lignin synthesis gas catalyst, which is composed of active components and does not require a carrier.
[0008] The active components are Cd and Cd oxide, Cu and Cu oxide, Ni and Ni oxide, Co and Co oxide, Fe and Fe oxide, and the molar ratio of the active component elements Cd:Cu:Ni:Co:Ni is 1:0.5-1.5:0.5-1.5:0.5-1.5:0.5-1.5.
[0009] The present invention develops a highly active and highly stable non-precious metal catalyst, which uses solar energy as the only input energy, efficiently converts lignin into synthesis gas under mild conditions, and exhibits high synthesis gas selectivity and good catalyst reusability.
[0010] Preferably, the molar ratio of the active component elements Cd:Cu:Ni:Co:Ni is 1:1:1:1:1.
[0011] A method for preparing a solar-driven lignin-to-syngas catalyst according to the present invention comprises the following steps:
[0012] Step 1: Dissolve the calculated amount of metal source in isopropanol and stir thoroughly at room temperature until clear;
[0013] Step 2: dissolving the organic ligand glycerol in the solution obtained in step 1, and stirring thoroughly at room temperature until the solution becomes clear;
[0014] Step 3: Transfer the solution obtained in step 2 to a hydrothermal reactor and crystallize at 150°C-170°C for 10h-14h;
[0015] Step 4: Filter the solution obtained in step 3 at room temperature, and wash the solid powder with a detergent to remove impurities to obtain a precursor;
[0016] Step 5: Transfer the precursor obtained in step 4 to an evaporating dish and dry it at a temperature of 60°C-70°C to obtain a precursor solid powder;
[0017] Step 6: Dissolve the precursor solid powder left after drying in step 5 and the second organic ligand in anhydrous ethanol, and stir thoroughly at room temperature until clear;
[0018] Step 7: Transfer the solution obtained in step 6 to a hydrothermal reactor and crystallize at 150°C-170°C for 10h-14h;
[0019] Step 8: Filter the solution obtained in step 7 at room temperature, and wash the solid powder with a detergent to remove impurities, thereby obtaining a solar-driven lignin-to-syngas catalyst.
[0020] Preferably, the Cd source is cadmium nitrate, the Cu source is copper nitrate, the Ni source is nickel nitrate, the Co source is cobalt nitrate, the Fe source is iron nitrate, the second organic ligand is thioacetamide, and the detergent is one or more of anhydrous ethanol, anhydrous methanol or water.
[0021] Preferably, the amount of the second organic ligand thioacetamide and anhydrous ethanol is 0.3 g-0.4 g:100 mL. Most preferably, the amount of the second organic ligand thioacetamide and anhydrous ethanol is 0.33 g:100 mL.
[0022] Preferably, in step 2, the volume ratio of isopropanol to glycerol is 34:6;
[0023] The crystallization method in steps 3 and 7 is as follows: the obtained solution is transferred to a hydrothermal reactor, and then moved to an oven, the temperature is set to 160°C, and the crystallization time is 12h;
[0024] The precursor drying method in step 5 is: transfer the obtained precursor to an evaporating dish, and move it into an oven, set the temperature to 65° C., and the drying time to 14 h.
[0025] Preferably, the preparation method further comprises step nine: transferring the precursor obtained in step eight to an evaporating dish and drying at a temperature of 60°C-70°C to obtain a solid powder of a solar-driven lignin-to-syngas catalyst. Preferably, the drying in step nine is: drying in an oven at 60°C for 24 hours.
[0026] A use of the solar-driven lignin-to-syngas catalyst in solar-driven lignin-to-syngas production.
[0027] Preferably, the reaction conditions for the solar-driven lignin synthesis gas are: the reaction light intensity is 3.5-7.5 W / cm 2 , the water content of lignin is 0-24wt%. Generally, the reaction pressure is 1 atmosphere.
[0028] As a preference, the reaction light intensity is 6.5-7.5 W / cm under concentrated light conditions. 2 , the moisture content of lignin is 0-12wt%. The optimal solution is that the reaction light intensity is 7.5W / cm 2 , the moisture content of lignin is 6wt%.
[0029] The catalyst preparation of the present invention adopts a hot solvent method to induce a self-assembly pathway to synthesize a solar-driven lignin-generated synthesis gas catalyst. It should be particularly noted that the solvent isopropanol and the organic ligand glycerol in the method of the present invention play an extremely important role. The ligand glycerol complexes with metal ions to promote the formation of metal glycerol salts (precursor solid powders), while the solvent isopropanol promotes the formation and dispersion of metal glycerol salt microspheres. The volume ratio of isopropanol to glycerol in the method of the present invention is 34:6. The absence of both makes it impossible to successfully synthesize the catalyst described in the present invention. The present invention has the following advantages:
[0030] 1. The solar-driven lignin-to-syngas catalyst provided by the present invention is a mesoporous composite metal sulfide, which has a simple preparation method and is easy to operate. The raw materials are cheap and readily available non-precious metal salts, and are used for solar-driven lignin-to-syngas;
[0031] 2. The catalyst provided by the present invention is used for solar-driven lignin synthesis gas production, with a synthesis gas production rate of up to 129.24 mmol / g / h and a selectivity of gas and biochar of 72.07%;
[0032] 3. The solar-driven lignin-to-syngas catalyst provided by the present invention, when applied to specific biomass, such as wheat straw, corn straw, and rice straw, still has good syngas production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can also obtain other drawings based on these drawings without paying any creative work.
[0034] Figure 1 This is a SEM photo of the catalyst product precursor of Example 1;
[0035] Figure 2 XRD images, where the left image is the catalyst product and catalyst precursor of Example 1, and the right image is Examples 2-4;
[0036] Figure 3 This is the XPS picture of the catalyst product of Example 1;
[0037] Figure 4 This is a process flow chart of the preparation of a solar-driven lignin-to-syngas catalyst according to the present invention;
[0038] Figure 5 N2 adsorption-desorption curves of the catalyst and precursor products of Example 1;
[0039] Figure 6 The absorption characteristics of ultraviolet, visible and near-infrared light of the catalyst products of Examples 1-4 are shown;
[0040] Figure 7 This is a stability test chart of the catalyst product of Example 1 after continuous reaction for 12 hours. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification or change made to the present invention will fall within the protection scope of the present invention.
[0042] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0043] A quartz reactor was used to test the performance of the catalyst, and the gas phase product was analyzed using a GC2060 gas chromatograph from Shanghai Minrui Instrument Co., Ltd. A 300W xenon lamp simulating sunlight was used as the light source in the reaction.
[0044] Example 1
[0045] A method for preparing a solar-driven lignin synthesis gas catalyst, the process flow chart is as follows Figure 5 As shown, the specific steps are as follows:
[0046] Accurately weigh 0.202 g of ferric nitrate nonahydrate, 0.116 g of copper nitrate trihydrate, 0.145 g of nickel nitrate hexahydrate, 0.145 g of cobalt nitrate hexahydrate, and 0.154 g of cadmium nitrate tetrahydrate, add them to 34 mL of isopropanol, stir and dissolve thoroughly, and after dissolution, accurately measure 6 mL of glycerol, drip it dropwise into the above solution, stir and dissolve thoroughly until it is clear, transfer the prepared precursor solution to a 100 mL hydrothermal reactor, and place it in a 160 ° C oven for crystallization for 12 h. After sufficient crystallization, filter the solution obtained in the hydrothermal reactor and wash it with anhydrous ethanol to obtain a catalyst precursor (SEM photo as shown in FIG. Figure 1 shown).
[0047] The prepared precursor was transferred to an evaporating dish and placed in a 65°C oven for drying for 14 hours to obtain a precursor powder. 0.1g of the precursor powder and 0.165g of thioacetamide were added to 50ml of anhydrous ethanol solution, and fully stirred and dissolved until clear. The prepared precursor solution was transferred to a 100mL hydrothermal reactor and placed in a 160°C oven for crystallization for 12 hours. After sufficient crystallization, the solution obtained in the hydrothermal reactor was filtered and washed with anhydrous ethanol to obtain a high entropy sulfide catalyst. Due to the large entropy value, the catalyst prepared in this experiment is an amorphous material (XRD diagram as shown in Figure 2 The valence states of each element are shown in Figure 3 shown.
[0048] In the catalyst prepared in this example, the molar ratio of the active component elements Cd:Cu:Ni:Co:Ni is 1:1:1:1:1.
[0049] Example 2
[0050] A method for preparing syngas from lignin driven by solar energy, the specific steps are as follows:
[0051] Accurately weigh 0.202 g of ferric nitrate nonahydrate, 0.116 g of copper nitrate trihydrate, 0.145 g of cobalt nitrate hexahydrate, and 0.154 g of cadmium nitrate tetrahydrate, add them to 34 mL of isopropanol, and stir thoroughly to dissolve. After dissolution, accurately measure 6 mL of glycerol, dropwise add it into the above solution, stir thoroughly to dissolve until clear, transfer the prepared precursor solution to a 100 mL hydrothermal reactor, and place it in a 160°C oven for crystallization for 12 hours. After sufficient crystallization, filter the suspension obtained in the hydrothermal reactor and wash it with anhydrous ethanol to obtain a catalyst precursor. The prepared precursor was transferred to an evaporating dish, placed in an oven at 65°C, and dried for 14 hours to obtain a precursor powder. 0.1 g of the precursor powder and 0.165 g of thioacetamide were added to 50 ml of anhydrous ethanol solution and stirred thoroughly to dissolve until clear. The prepared precursor solution was transferred to a 100 mL hydrothermal reactor and placed in an oven at 160°C for crystallization for 12 hours. After sufficient crystallization, the solution obtained in the hydrothermal reactor was filtered and washed with anhydrous ethanol to obtain sulfide catalyst 2.
[0052] Example 3
[0053] A method for preparing a solar-driven lignin-to-syngas catalyst, the specific steps are as follows:
[0054] Accurately weigh 0.116 g of copper nitrate trihydrate, 0.145 g of cobalt nitrate hexahydrate, and 0.154 g of cadmium nitrate tetrahydrate, add them to 34 mL of isopropanol, and stir thoroughly to dissolve. After dissolution, accurately measure 6 mL of glycerol, dropwise add it into the above solution, stir thoroughly to dissolve until clear, transfer the prepared precursor solution to a 100 mL hydrothermal reactor, and place it in a 160°C oven for crystallization for 12 hours. After sufficient crystallization, filter the suspension obtained in the hydrothermal reactor and wash it with anhydrous ethanol to obtain a catalyst precursor. The prepared precursor was transferred to an evaporating dish and placed in an oven at 65°C for drying for 14 hours to obtain a precursor powder. 0.1 g of the precursor powder and 0.165 g of thioacetamide were added to 50 ml of anhydrous ethanol solution and stirred thoroughly to dissolve until clear. The prepared precursor solution was transferred to a 100 mL hydrothermal reactor and placed in an oven at 160°C for crystallization for 12 hours. After sufficient crystallization, the solution obtained in the hydrothermal reactor was filtered and washed with anhydrous ethanol to obtain sulfide catalyst 3.
[0055] Example 4
[0056] A method for preparing a solar-driven lignin-to-syngas catalyst, the specific steps are as follows:
[0057] Accurately weigh 0.116g of copper nitrate trihydrate and 0.154g of cadmium nitrate tetrahydrate, add them to 34mL of isopropanol, stir and dissolve thoroughly, after dissolving, accurately measure 6mL of glycerol, drip into the above solution drop by drop, stir and dissolve thoroughly until clear, transfer the prepared precursor solution to a 100mL hydrothermal reactor, and place it in a 160℃ oven for crystallization for 12h, after sufficient crystallization, filter the suspension obtained in the hydrothermal reactor, and wash with anhydrous ethanol to obtain a catalyst precursor. Transfer the prepared precursor to an evaporating dish, place it in a 65℃ oven, and dry it for 14h to obtain a precursor powder. Take 0.1g of the precursor powder and 0.165g of thioacetamide, add them to 50ml of anhydrous ethanol solution, stir and dissolve until clear, transfer the prepared precursor solution to a 100mL hydrothermal reactor, and put it in a 160°C oven for crystallization for 12h. After sufficient crystallization, filter the solution obtained in the hydrothermal reactor and wash with anhydrous ethanol to obtain sulfide catalyst 4.
[0058] Application Example 1
[0059] 120 mg of the catalyst prepared in Example 1, Example 2, Example 3, and Example 4 were respectively ground and mixed with 150 mg of lignin and then placed in a reactor. The reactor was sealed, vacuumed and argon was introduced for five times, and the air in the reactor was exhausted and argon was finally introduced. A light source with an intensity of 7.5 W / cm 2, the reaction started for 5 minutes. After the reaction was completed, the obtained synthesis gas was analyzed by gas chromatography. The specific results are shown in Table 1.
[0060] Table 1 Comparison of the activity of solar-driven lignin-to-syngas catalysts
[0061]
[0062]
[0063] Application Example 2
[0064] 120 mg of the catalyst prepared in Example 1 and 150 mg of lignin were ground and mixed thoroughly, and then placed in a reactor. The reactor was sealed, vacuumed and argon was introduced for five times, and the air in the reactor was exhausted and argon was introduced. A light source was introduced and the intensity of the light source was adjusted to 3.5 W / cm 2 , 4.5W / cm 2 , 5.5W / cm 2 、6.5W / cm 2 , 7.5W / cm 2 , the reaction started for 5 minutes. After the reaction was completed, the obtained synthesis gas was analyzed by gas chromatography. The specific results are shown in Table 2.
[0065] Table 2 Effect of light intensity on lignin synthesis gas production
[0066]
[0067] Application Example 3
[0068] 120 mg of the catalyst prepared in Example 1 was ground and mixed with 150 mg of lignin, and then placed in a reactor. The reactor was sealed, vacuumed and introduced with argon, and repeated five times. The air in the reactor was exhausted and argon was finally introduced. Deionized water with mass fractions of 0, 6, 12, 18, and 24 wt% was injected into the reactor under an argon atmosphere. A light source with an intensity of 7.5 W / cm 2 , the reaction started for 5 minutes. After the reaction was completed, the obtained synthesis gas was analyzed by gas chromatography. The specific results are shown in Table 3.
[0069] Table 3 Effect of deionized water content on synthesis gas production
[0070]
[0071]
[0072] Application Example 4
[0073] 120 mg of the catalyst prepared in Example 1 and 150 mg of lignin were ground and mixed well and then placed in a reactor. The reactor was sealed, vacuumed and argon was introduced five times, the air in the reactor was exhausted, and argon was finally introduced. The heating temperature of the thermocouple was set to 470°C, which was the same as the temperature provided by the light source intensity in Application Example 3. The reaction was started for 5 minutes. After the reaction was completed, the obtained synthesis gas was analyzed by gas chromatograph. The specific results are shown in Table 4.
[0074] Table 4 Comparison of thermal reaction activity of lignin-to-syngas catalysts
[0075]
[0076] N2 adsorption-desorption experiment
[0077] The specific method of N2 adsorption-desorption test is:
[0078] 1. Weigh about 100 mg of sample and add it into a 9 mm diameter BET sample tube;
[0079] 2. Place the sample tube into the degassing station and degas at 120℃ for more than 12 hours;
[0080] 3. Use QUADRASORB EVO specific surface area and pore size analyzer to conduct N2 adsorption-desorption test on catalyst products.
[0081] The above test was carried out on the catalyst product and its precursor obtained in Example 1, and the obtained N2 adsorption-desorption curve was as follows: Figure 5 shown.
[0082] according to Figure 5 From the data, it can be seen that the adsorption-desorption isotherms of the series of catalysts synthesized by this method show typical type IV isotherms, indicating that the catalyst has a mesoporous structure and the mesopore diameter ranges from 2 to 60 nm.
[0083] according to Figure 6 From the data, it can be seen that the series of catalysts synthesized by this method have an absorption rate of over 90% for full-band sunlight, and the band gap of the catalyst gradually decreases with the increase of catalyst components, with the lowest being 0.79eV, which indicates that more sunlight in longer bands can be utilized.
[0084] according to Figure 7 The data show that the catalyst synthesized by this method has excellent stability.
[0085] As shown in Table 1, the rate of syngas production gradually increases from low, medium to high entropy of the catalyst, while the selectivity of syngas gradually increases and the selectivity of tar by-products decreases. As shown in Table 2, the rate of syngas production gradually increases with the increase of light intensity. As can be seen from Table 3, with the increase of deionized water, the rate of syngas production first increases and then decreases. When the mass fraction of deionized water is 6wt%, the rate of syngas production gradually increases. As can be seen from Table 4, the rate of photocatalytic syngas production is higher than the rate of syngas production by thermal reaction, indicating that the catalyst synthesized by this method can make full use of sunlight to drive the reaction, which is more energy-saving and environmentally friendly.
[0086] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
Claims
1. A solar-driven lignin-to-syngas catalyst, characterized in that: The catalyst is composed of active components and does not require a carrier. The active components are Cd and Cd oxide, Cu and Cu oxide, Ni and Ni oxide, Co and Co oxide, Fe and Fe oxide, and the molar ratio of the active component elements Cd:Cu:Ni:Co:Ni is 1:0.5-1.5:0.5-1.5:0.5-1.5:0.5-1.
5.
2. The solar-driven lignin-to-syngas catalyst according to claim 1, characterized in that: The molar ratio of active component elements Cd:Cu:Ni:Co:Ni is 1:1:1:1:
1.
3. A method for preparing a solar-driven lignin-to-syngas catalyst according to claim 1, characterized in that The method comprises the following steps: Step 1: Dissolve the calculated amount of metal source in isopropanol and stir thoroughly at room temperature until clear; Step 2: dissolving the organic ligand glycerol in the solution obtained in step 1, and stirring thoroughly at room temperature until the solution becomes clear; Step 3: Transfer the solution obtained in step 2 to a hydrothermal reactor and crystallize at 150°C-170°C for 10 h-14 h; Step 4: Filter the solution obtained in step 3 at room temperature, and wash the solid powder with a detergent to remove impurities to obtain a precursor; Step 5: Transfer the precursor obtained in step 4 to an evaporating dish and dry it at a temperature of 60°C-70°C to obtain a precursor solid powder; Step 6: Dissolve the precursor solid powder left after drying in step 5 and the second organic ligand in anhydrous ethanol, and stir thoroughly at room temperature until clear; Step 7: Transfer the solution obtained in step 6 to a hydrothermal reactor and crystallize at 150°C-170°C for 10 h-14 h; Step 8: Filter the solution obtained in step 7 at room temperature, and wash the solid powder with a detergent to remove impurities, thereby obtaining a solar-driven lignin-to-syngas catalyst.
4. The preparation method according to claim 3, characterized in that: The Cd source is cadmium nitrate, the Cu source is copper nitrate, the Ni source is nickel nitrate, the Co source is cobalt nitrate, and the Fe source is iron nitrate. The second organic ligand is thioacetamide, and the detergent is one or more of anhydrous ethanol, anhydrous methanol or water.
5. The preparation method according to claim 3, characterized in that: The dosage of the second organic ligand thioacetamide and anhydrous ethanol is 0.3 g-0.4 g:100 mL.
6. The preparation method according to claim 3, characterized in that: In step 2, the volume ratio of isopropanol to glycerol is 34:6; The crystallization method in steps 3 and 7 is as follows: the obtained solution is transferred to a hydrothermal reactor, and then moved to an oven, the temperature is set to 160 °C, and the crystallization time is 12 h; The precursor drying method in step five is: the obtained precursor is transferred to an evaporating dish, and moved into an oven, the temperature is set to 65 ° C, and the drying time is 14 h.
7. The preparation method according to claim 3, characterized in that The preparation method further comprises step nine: transferring the precursor obtained in step eight to an evaporating dish, and drying at a temperature of 60° C.-70° C. to obtain a solar-driven lignin-to-syngas catalyst solid powder.
8. Use of the solar-driven lignin-to-syngas catalyst according to claim 1 in solar-driven lignin-to-syngas production.
9. The use according to claim 8, characterized in that: The reaction conditions of solar-driven lignin synthesis gas are: the reaction light intensity is 3.5-7.5 W / cm 2 , the moisture content of lignin is 0-24 wt%.
10. The use according to claim 8, characterized in that: Under concentrated light conditions, the reaction light intensity is 6.5-7.5 W / cm 2 , the moisture content of lignin is 0-12 wt%.